Management of Parenting Activities in Forming Character of Early Childhood - Hefniy Hefniy; Anggie Nadia Dinihari; Fathor Rozi; Nur Aini; Afifah Tunnaja (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to analyze parenting activities in shaping the character of early childhood at Taman Posyandu Anak Salih. The research method used is a qualitative case study type. Researchers conducted interviews with principals and teachers at the institution. The study results indicate that the formation of children's character requires a continuous and consistent process, both when the child is in the family environment, school environment, and community environment. Schools in approaching parents through parenting activities are carried out through; 1) planning includes determining the time, place of materials, and media needed in parenting activities; 2) implementation, namely the form of parental meetings or parent classes by prioritizing the discussion and sharing process; 3) evaluation in the parenting program using question and answer according to the material that has been conveyed with parents and meetings regarding ongoing programs conducted by educators and managers so that parents become partners in the formation of children's character.